Economics of rice production in Pyuthan district of Nepal - Bhusal, Sagar; Karn, Rupak; Jha, Ritesh Kumar; Ojha, Ankit (Journal of Agriculture and Natural Resources, 2020)
A research was conducted at Pyuthan district in order to access the profitability of rice production in Pyuthan during the summer season of 2018-2019. Altogether of 70 respondents were selected randomly and surveyed with semi-structured interview schedule. The results revealed that the average land holding was 0.45 hectare, and the average rice cultivation area was 0.34 hectare. On the basis of average rice cultivation area, farmers were categorized as small (39) and large (31). The cost and return was calculated among both the category. t- test was used to compare the mean costs of inputs between small and large farmers. Cost for agronomic operations was found far higher (more than 70%) in both the category in compared to the cost of inputs. Contribution of rice grains and straw to overall return was 72.65% and 27.35% respectively. Benefit Cost ratio was found greater among large farmers. The average B:C ratio was 1.51, which was fairly higher than 1.14 in Dang district indicating the investment of rice production is expected to deliver a positive net return to the farmers of the study area. In a nutshell, rice cultivation is an important enterprise that should be encouraged, considering the fact that it is a major staple crop.